Lithium metal battery, manufacturing method thereof and electric equipment
By constructing a composite interface layer and a flexible organic layer through a phased liquid injection process, the lithium deposition behavior is synergistically regulated, which solves the interface instability problem of negative electrode-free lithium metal batteries and realizes lithium metal batteries with high energy density and long cycle stability.
Patent Information
- Application Number
- CN202511119374.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-24
- Publication Date
- 2025-10-10
AI Technical Summary
The negative electrode of the negative electrode-free lithium metal battery faces the problem of interface instability, which leads to severe lithium dendrite growth and interface side reactions, limiting the energy density and cycle stability of the battery.
A staged injection process is adopted. The first injection forms a sulfur-nitrogen synergistic composite inorganic interface layer, and the second injection introduces a flexible organic layer and functional additives. The lithium ion deposition path is synergistically regulated through electrostatic shielding and anchoring filling additives to optimize the interface morphology and stability.
It improves the interface stability and long cycle performance of lithium metal batteries, inhibits the growth of lithium dendrites, and improves the cycle stability and energy density of batteries at high rates.
Smart Images

Figure CN120767435A_ABST
Abstract
Description
[0001] Cross Reference to Related Applications
[0002] This application is a divisional application of the patent application with the application date of June 24, 2025, application number 202510854769.8, and invention name “Lithium metal battery, manufacturing method thereof, and electrical equipment”. Technical Field
[0003] The present application relates to the field of lithium metal batteries, and in particular to a lithium metal battery, a manufacturing method thereof, and electrical equipment. Background Art
[0004] With the rapid development of renewable energy, the energy density of energy storage batteries has become a key factor in determining technological competitiveness. The energy density of traditional lithium-ion batteries has gradually increased from an initial 100Wh / kg to 250Wh / kg to 300Wh / kg. However, this progress has reached its theoretical limit, and further improvement faces significant challenges. Against this backdrop, lithium metal batteries have emerged as a key technological path to breaking through the energy density bottleneck.
[0005] Lithium metal batteries use manganese dioxide as the positive electrode material, metallic lithium or alloy metals as the negative electrode material, and a non-aqueous electrolyte solution. Lithium metal negative electrodes offer significant advantages over traditional graphite negative electrodes. The theoretical specific capacity of lithium metal negative electrodes is as high as 3860 mAh / kg, 10 times that of graphite negative electrodes (372 mAh / kg). This helps increase battery voltage, and the manufacturing process is simple, which helps reduce the complexity of the electrode structure. The basic operating principles of negative electrode-free lithium metal batteries and traditional lithium metal negative electrode batteries are actually highly consistent. Both are based on the reciprocating migration of lithium ions between the positive and negative electrodes. During charging, lithium ions are deintercalated from the positive electrode and deposited as metallic lithium on the surface of the negative electrode. During discharge, the metallic lithium oxidizes and returns to the positive electrode. The difference is that in negative electrode-free lithium metal batteries, the negative electrode sheet is composed of a current collector, which further simplifies the electrode design and increases the energy density to 350 Wh / kg to 400 Wh / kg.
[0006] However, the interfacial instability problem faced by the negative electrode sheets of negative electrode-free lithium metal batteries remains severe. Summary of the Invention
[0007] The embodiments of the present application provide a lithium metal battery, a method for manufacturing the same, and an electrical device, which are at least beneficial for improving the stability of the negative electrode-free lithium metal battery.
[0008] According to some embodiments of the present application, on the one hand, an embodiment of the present application provides a method for manufacturing a lithium metal battery, comprising: providing a positive electrode sheet, a negative electrode current collector and a separator, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer; winding or laminating the positive electrode sheet, the negative electrode current collector and the separator and placing them into a shell to form a battery cell assembly, wherein the separator is located between the positive electrode sheet and the negative electrode current collector; performing a first liquid injection process on the battery cell assembly, injecting a first electrolyte into the battery cell assembly, wherein the components of the first electrolyte include: 0.1wt% to 5wt% of lithium polysulfide, 0.1wt% to 5wt% lithium nitrate, 5wt% to 15wt% lithium salt and the balance non-aqueous organic solvent; performing a first formation process on the battery cell assembly; performing a second liquid injection process on the battery cell assembly, injecting a second electrolyte into the battery cell assembly, the components of the second electrolyte including: 5wt% to 35wt% fluoroethylene carbonate, 5wt% to 15wt% lithium salt, 0.05wt% to 20wt% electrostatic shielding additive, 0.05wt% to 20wt% anchoring filling additive and the balance non-aqueous organic solvent; performing a second formation process on the battery cell assembly.
[0009] In some embodiments, the non-aqueous organic solvent in the first electrolyte includes an ether-based solvent, and the weight ratio of the ether-based solvent to the weight ratio of the non-aqueous organic solvent is greater than 50 wt %.
[0010] In some embodiments, the non-aqueous organic solvent in the second electrolyte includes an ether-based solvent and a sulfone-based solvent, and the total weight of the ether-based solvent and the sulfone-based solvent accounts for more than 50 wt % of the total weight of the non-aqueous organic solvent.
[0011] In some embodiments, in the second electrolyte, a mass ratio of the ether-based solvent to the sulfone-based solvent is greater than or equal to 1.
[0012] In some embodiments, the first formation process includes: charging the battery cell assembly to a state of charge greater than or equal to 50% at a first charging rate and a first temperature; the second formation process includes: charging the battery cell assembly to a state of charge greater than 85% at a second charging rate and a second temperature; wherein the first charging rate is less than the second charging rate, and the first temperature is less than the second temperature.
[0013] In some embodiments, the first charging rate is 0.01C to 0.2C; the second charging rate is 0.2C to 0.5C; the first temperature is 40°C to 50°C; and the second temperature is 40°C to 50°C.
[0014] In some embodiments, the anchoring filler additive is selected from at least one of a fullerene derivative, an organosilicon compound, or a carbon-based nanomaterial.
[0015] In some embodiments, the electrostatic shielding additive is selected from at least one of an organic quaternary ammonium salt, a metal halide, or an organic ionic liquid.
[0016] In some embodiments, the negative current collector is selected from one of a copper foil, a nano-coated copper, a copper foam, a copper mesh, a metal-carbon composite current collector, or a lithium intercalation alloy-based current collector.
[0017] In some embodiments, the material of the positive material layer includes at least one of a layered oxide material, a spinel structure material, a polyanion material, a lithium-rich manganese-based material, a transition metal fluoride material, or an organic material.
[0018] According to some embodiments of the present application, another aspect of the embodiments of the present application further provides a lithium metal battery prepared by using the manufacturing method of the lithium metal battery in the above embodiments.
[0019] According to some embodiments of the present application, still another aspect of the embodiments of the present application further provides a load device, which includes the lithium metal battery in the above embodiments and a load; or, the load device includes an energy storage system and a load, and the energy storage system includes a plurality of lithium metal batteries in the above embodiments.
[0020] The technical solutions provided by the embodiments of the present application have at least the following advantages:
[0021] In the manufacturing method of the lithium metal battery provided by the embodiments of the present application, the positive sheet includes a positive current collector and a positive material layer, and the negative sheet includes a negative current collector, to form a negative electrode-free lithium metal battery. After assembling the positive sheet, the negative current collector, and a separator into a battery cell assembly, an inorganic-organic composite interface layer is constructed and the lithium deposition behavior is dynamically regulated by injecting electrolyte in stages. The first injection forms a rigid composite inorganic interface layer, and the second injection superimposes a flexible organic layer and introduces a functional additive, to systematically solve the interface stability and lithium dendrite growth problems. Based on the dynamic requirements of the interface of the negative electrode-free lithium metal battery, the first injection focuses on constructing a high-stability composite inorganic interface layer to reduce the initial side reaction activity; the second injection uses a flexible organic film and a dynamic regulation dual-path to continuously optimize the deposition behavior and repair interface defects. The synergistic design of the two-step process takes into account the interface rigidity support and dynamic adaptability, providing dual protection for long-cycle stability and high-rate performance.
[0022] In the first injection process, a first electrolyte consisting of lithium polysulfide (Li2S8), lithium nitrate (LiNO3), lithium salt, and non-aqueous organic solvent is injected into the battery cell assembly, followed by a first formation process. The complementary properties of lithium polysulfide and lithium nitrate are used to form a composite inorganic interface layer. The sulfide layer (Li2S) formed by Li2S8 is mechanically brittle and easily fractured due to stress concentration. The nitride layer (Li3N) formed by LiNO3, while chemically stable, has poor adaptability to volume expansion. Through the synergistic effect of Li2S8 and LiNO3, a sulfur-nitrogen composite mechanism is used to form a Li2S-Li3N cross-linked structure, which combines high ionic conductivity and mechanical toughness. This not only inhibits electrolyte decomposition but also provides a stable foundation for subsequent cycles. In the second injection process, a second electrolyte consisting of fluoroethylene carbonate (FEC), lithium salt, electrostatic shielding additives, anchoring filler additives, and non-aqueous organic solvent is injected into the battery cell assembly, followed by a second formation process. A flexible organic layer is generated through FEC decomposition and coated on the surface of the composite inorganic interface layer to alleviate the stress impact caused by volume changes. Its dynamic repair properties can adapt to the stress changes caused by the volume expansion / contraction of lithium metal, reducing the risk of interfacial film rupture. The second injection process also introduces electrostatic shielding additives and anchoring filler additives. The electrostatic shielding additive releases high-valent cations to neutralize the local electric field distortion in the lithium deposition raised area, balance the local electric field distribution, inhibit the excessive deposition of lithium ions in the raised area, block the dendrite nucleation path and thus block the growth of dendrite tips. The anchoring filler additive guides lithium ions through adsorption and directional deposition at defect sites, preferentially guiding the formation of a dense lithium layer in the depressed area of the interface, promoting a uniform deposition morphology. Electrostatic shielding additives are used to suppress the tip effect, and anchoring filling additives repair interface defects. Electrostatic shielding additives and anchoring filling additives work together to guide the directional deposition of lithium ions through physical confinement and chemical bonding, repairing microscopic defects, not only achieving uniform lithium deposition morphology, but also reducing interface impedance and optimizing ion transfer kinetics. The synergistic effect of electrostatic shielding additives and anchoring filling additives breaks through the limitation of a single type of additive that only regulates local deposition, and reduces interface impedance and optimizes lithium ion transfer kinetics through complementary mechanisms, thereby improving the cycle stability of lithium metal batteries at high rates. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] One or more embodiments are exemplarily illustrated by the pictures in the corresponding drawings. These exemplified descriptions do not constitute a limitation on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute a scale limitation. In order to more clearly illustrate the embodiments of the present application or the technical solutions in the traditional technology, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 This is a flowchart corresponding to the method for manufacturing a lithium metal battery provided in one embodiment of the present application. DETAILED DESCRIPTION
[0025] As known from the background art, the negative electrode sheet of the negative electrode-less lithium metal battery has the problem of interface instability.
[0026] Faced with the potential advantages of lithium metal batteries, researchers have explored various technical approaches to address their inherent shortcomings. These approaches primarily include current collector surface modification, artificial interface membrane construction, and three-dimensional current collector design, attempting to improve lithium metal deposition behavior and interfacial stability from different perspectives. However, these approaches require complex manufacturing processes or fundamental changes to the electrode structure, significantly increasing the difficulty and cost of implementation.
[0027] Among numerous technical approaches, electrolyte optimization offers unique advantages. Compared to other approaches, it boasts simpler processes, lower modification costs, and ease of large-scale industrial application. By adjusting electrolyte composition, it can directly act on the negative electrode interface of lithium metal batteries, regulating lithium deposition behavior at the molecular scale, making it the technical approach with the greatest commercial potential.
[0028] Because lithium metal has a volume expansion rate of approximately 300%, its deposition behavior is extremely uneven, making it prone to the formation of lithium dendrites. Under high-rate charge and discharge conditions, the uneven local current density makes it difficult to control the lithium deposition morphology and leads to severe interfacial side reactions, which restricts the practical application of batteries.
[0029] Conventional single-shot electrolyte injection strategies have significant limitations. During the initial film formation phase, additives tend to react unevenly; during long-term cycling, the interfacial film struggles to adapt to volume changes. The film formation potentials of different additives vary significantly, making it impossible to precisely control the interfacial film quality. This has prevented the performance of lithium metal anode batteries, or anode-free lithium metal batteries, from breaking through key bottlenecks.
[0030] Therefore, a phased optimization of the electrolyte solution is urgently needed to simultaneously meet two key requirements: ensuring uniformity, stability, and mechanical strength of the initial film formation, and ensuring the flexibility of the interfacial film during long-term cycling. By precisely controlling lithium deposition behavior and inhibiting lithium dendrite growth, it is hoped that the core technical challenges that have hindered the development of lithium metal batteries will be fundamentally resolved.
[0031] An embodiment of the present application provides a lithium metal battery, a manufacturing method thereof, and an electrical device. In the manufacturing method of the lithium metal battery, a positive electrode sheet, a negative electrode current collector, and a separator are assembled into a battery cell assembly. The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer. The negative electrode current collector is used as the negative electrode sheet to form a negative electrode-free lithium metal battery.
[0032] By injecting electrolyte in stages to adapt to the interface requirements, the first liquid injection is used to construct a sulfur-nitrogen synergistic composite inorganic interface layer, which inhibits initial dendrite nucleation and side reactions and provides mechanical support; the second liquid injection is used to introduce high-concentration fluoroethylene carbonate to form a flexible organic layer, and electrostatic shielding additives and anchoring filling additives are introduced to dynamically regulate the deposition path of lithium ions, quickly achieve uniform interface morphology, and optimize the long-term cycle performance of lithium metal batteries.
[0033] The two-step injection design avoids the conflict between the additive functions and the film-forming potential in a single injection, while taking into account the process feasibility and large-scale production cost control, providing a reliable technical path for the commercialization of negative-electrode-free lithium metal batteries.
[0034] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0035] In the description of the embodiments of the present application, “multiple” means more than two, unless otherwise clearly and specifically defined.
[0036] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0037] In the description of the embodiments of the present application, when a component “includes” another component, unless otherwise stated, other components are not excluded, and other components may be further included.
[0038] The terms used in the description of the various embodiments described herein are for describing specific embodiments only and are not intended to be limiting. As used in the description of the various embodiments described and the appended claims, "components" are also intended to include plural forms unless the context clearly indicates otherwise.
[0039] The following detailed description of the various embodiments of the present application is provided in conjunction with the accompanying drawings. However, those skilled in the art will appreciate that many technical details are provided in the various embodiments of the present application to facilitate a better understanding of the present application. However, even without these technical details and the various variations and modifications based on the following embodiments, the technical solutions claimed in the present application can still be implemented.
[0040] Figure 1This is a flowchart corresponding to the method for manufacturing a lithium metal battery provided in one embodiment of the present application.
[0041] refer to Figure 1 , the manufacturing method of the lithium metal battery provided in the embodiment of the present application is as follows.
[0042] S101. Provide a positive electrode sheet, a negative electrode current collector and a separator. The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer.
[0043] S102 , winding or stacking the positive electrode sheet, the negative electrode current collector, and the separator and placing them into a shell to form a battery cell assembly, with the separator being located between the positive electrode sheet and the negative electrode current collector.
[0044] S103. Perform a first liquid injection process on the battery cell assembly, injecting a first electrolyte into the battery cell assembly, wherein the components of the first electrolyte include: 0.1wt% to 5wt% of lithium polysulfide, 0.1wt% to 5wt% of lithium nitrate, 5wt% to 15wt% of lithium salt and the remainder of non-aqueous organic solvent.
[0045] S104, performing a first formation process on the battery cell assembly.
[0046] S105. Perform a second liquid injection process on the battery cell assembly, injecting a second electrolyte into the battery cell assembly, wherein the components of the second electrolyte include: 5wt% to 35wt% of fluoroethylene carbonate, 5wt% to 15wt% of lithium salt, 0.05wt% to 20wt% of electrostatic shielding additive, 0.05wt% to 20wt% of anchoring filling additive and the remainder of non-aqueous organic solvent.
[0047] S106, performing a second formation process on the battery cell assembly.
[0048] In the manufacturing method of the lithium metal battery provided in the embodiment of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer, and the negative electrode current collector is used as the negative electrode sheet to form a negative electrode-free lithium metal battery. After the positive electrode sheet, the negative electrode current collector and the separator are assembled into a battery cell component, the inorganic-organic composite interface layer is constructed by injecting electrolyte in stages and the lithium deposition behavior is dynamically regulated. The first injection forms a rigid composite inorganic interface layer, and the second injection superimposes a flexible organic layer and introduces functional additives to systematically solve the problems of interface stability and lithium dendrite growth. Based on the interface dynamic requirements of the negative electrode-free lithium metal battery, the first injection focuses on constructing a high-stability composite inorganic interface layer to reduce the initial side reaction activity; the second injection continuously optimizes the deposition behavior and repairs interface defects through a flexible organic film and dynamic regulation dual path. The collaborative design of the two-step process takes into account both interface rigid support and dynamic adaptability, providing double guarantees for long-cycle stability and high-rate performance.
[0049] In the first injection process, a first electrolyte consisting of lithium polysulfide (Li2S8), lithium nitrate (LiNO3), a lithium salt, and a non-aqueous organic solvent is injected into the battery cell assembly. This is followed by a first formation process, where the complementary properties of lithium polysulfide and lithium nitrate are utilized to form a composite inorganic interface layer. The sulfide layer (Li2S) formed by Li2S8 is mechanically brittle and prone to fracture due to stress concentration. The nitride layer (Li3N) formed by LiNO3, while chemically stable, has poor adaptability to volume expansion. Through the synergistic effect of Li2S8 and LiNO3, a sulfur-nitrogen composite mechanism is employed to form a Li2S-Li3N cross-linked structure, combining high ionic conductivity with mechanical toughness. This structure inhibits electrolyte decomposition and provides a stable foundation for subsequent cycling. In the second injection process, a second electrolyte including fluoroethylene carbonate (FEC), lithium salt, electrostatic shielding additive, anchoring filling additive and non-aqueous organic solvent is injected into the battery cell assembly, and then a second formation process is carried out. A flexible organic layer is generated by decomposition of FEC, which covers the surface of the composite inorganic interface layer to alleviate the stress shock caused by volume change. Its dynamic repair characteristics can adapt to the stress changes caused by the volume expansion / contraction of lithium metal and reduce the risk of interface film rupture. Electrostatic shielding additives and anchoring filling additives are also introduced in the second injection process. The electrostatic shielding additive releases high-valent cations to neutralize the local electric field distortion in the lithium deposition protrusion area, balance the local electric field distribution, inhibit the excessive deposition tendency of lithium ions in the protrusion area, block the dendrite nucleation path and thus block the growth of dendrite tips; the anchoring filling additive guides the lithium ions to form a dense lithium layer in the interface depression area through adsorption and directional deposition of defect sites, and promotes uniform deposition morphology. Electrostatic shielding additives are used to suppress the tip effect, and anchoring filling additives are used to repair interface defects. Electrostatic shielding additives and anchoring filling additives work together to guide the directional deposition of lithium ions through physical confinement and chemical bonding, repairing microscopic defects, not only achieving uniform lithium deposition morphology, but also reducing interface impedance and optimizing ion transfer kinetics. The synergistic effect of electrostatic shielding additives and anchoring filling additives breaks through the limitation of a single type of additive that only regulates local deposition, and reduces interface impedance and optimizes lithium ion transfer kinetics through complementary mechanisms, thereby improving the cycle stability of lithium metal batteries at high rates.
[0050] In step S101, the positive electrode current collector is aluminum foil or other conductive substrates suitable for high voltage systems. The materials of the positive electrode material layer include positive electrode active material, binder and conductive agent.
[0051] The positive electrode active material is selected from layered oxide positive electrode materials, spinel structure positive electrode materials, polyanion positive electrode materials, lithium-rich manganese-based positive electrode materials, transition metal fluoride positive electrode materials and organic positive electrode materials.
[0052] Among them, the chemical formula of the layered oxide positive electrode material can be Li xMO2 (M is a combination of transition metal elements such as Ni, Co, Mn, Al); the typical representative of spinel structure positive electrode materials is LiMn2O4, which has high safety and good rate performance; the general formula of polyanion positive electrode materials is Li x MPO4 (M is Fe, Mn, Co, V, etc.), among which LiFePO4 has been widely used due to its excellent cycle stability and safety; lithium-rich manganese-based positive electrode materials (Li x M y Mn z O2, M is Ni, Co, etc.) has attracted attention due to its high specific capacity and high safety; transition metal fluoride positive electrode materials (such as FeF3, CoF3) have a higher voltage platform and high energy density; organic positive electrode materials (such as polymers containing carbonyl or quinone groups) have become potential candidates due to their environmental friendliness and structural designability.
[0053] The adhesive is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR) or polyacrylic acid (PAA).
[0054] The conductive agent is selected from one or more of conductive carbon black, graphene, carbon nanotubes or graphite.
[0055] The negative electrode current collector is selected from copper foil, nano-coated copper, copper foam, copper mesh, metal-carbon composite current collector, or lithium-intercalated alloy-based current collector. Nano-coated copper can improve wettability and interfacial stability; three-dimensional structures such as copper foam and copper mesh can also improve wettability and interfacial stability; and metal-carbon composite current collectors can improve the conductivity and mechanical stability of the negative electrode.
[0056] Separators include polypropylene (PP), polyethylene (PE), ceramic-coated, high-strength polymer, and composite separators. PP and PE porous separators offer excellent mechanical strength and chemical stability. Ceramic-coated separators are made by coating PP or PE separators with ceramic materials, improving their high-temperature resistance and safety. High-strength polymer separators (such as aramid nanofiber separators) offer excellent puncture resistance and high-temperature resistance. Composite separators (such as coated separators containing solid electrolytes) can further enhance the stability of lithium deposition, reduce the risk of dendrite growth, and increase cycle life.
[0057] In step S102, the battery casing can be divided into cylindrical battery casing, prismatic battery casing, and soft-pack battery casing according to the battery type. Cylindrical battery casings are usually made of steel or aluminum alloy; prismatic battery casings are usually made of aluminum or steel; and soft-pack battery casings are usually made of aluminum-plastic composite film, which includes an outer layer (nylon / PET), an intermediate layer (aluminum foil), and an inner layer (PP heat-sealing layer).
[0058] In step S103, the mass fraction of lithium polysulfide in the first electrolyte can be 0.1 wt%, 0.5 wt%, 1 wt%, 1.4 wt%, 2 wt%, 2.6 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.3 wt%, 4.5 wt%, 4.9 wt%, or 5 wt%. The mass fraction of lithium polysulfide refers to the ratio of the mass of lithium polysulfide to the total mass of the first electrolyte.
[0059] The mass fraction of lithium nitrate in the first electrolyte can specifically be 0.1 wt%, 0.5 wt%, 1 wt%, 1.4 wt%, 2 wt%, 2.6 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.3 wt%, 4.5 wt%, 4.9 wt% or 5 wt%. The mass fraction of lithium nitrate refers to the ratio of the mass of lithium nitrate to the total mass of the first electrolyte.
[0060] The lithium salt in the first electrolyte can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP), preferably one or more of LiPF6, LiBF4, LiBOB, LiDFOB, LiTFSI and LiFSI.
[0061] The mass fraction of the lithium salt in the first electrolyte can be specifically 5wt%, 8wt%, 10wt%, 12wt%, 13wt% or 15wt%.The mass fraction of the lithium salt refers to the ratio of the mass of the lithium salt to the total mass of the first electrolyte.
[0062] The first electrolyte may also include a film-forming additive selected from at least one of unsaturated bond-containing cyclic carbonates, fluorinated cyclic carbonates, cyclic sulfonates, cyclic sulfates, nitrile compounds, sulfonate cyclic quaternary ammonium salts, silane borate, silane phosphate, or anisole. These additives can optimize the composition and structure of the interfacial film, enhance its mechanical properties, and improve lithium deposition behavior and uniformity, thereby enhancing the safety and cycling stability of lithium metal batteries.
[0063] The mass fraction of the film-forming additive in the first electrolyte can specifically be 0.1 wt%, 0.5 wt%, 1 wt%, 1.4 wt%, 2 wt%, 2.6 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.3 wt%, 4.5 wt%, 4.9 wt% or 5 wt%. The mass fraction of the film-forming additive refers to the ratio of the mass of the film-forming additive to the total mass of the first electrolyte.
[0064] The non-aqueous organic solvent in the first electrolyte may include an ether-based solvent, and the mass ratio of the ether-based solvent to the mass ratio of the non-aqueous organic solvent is greater than 50wt%, for example, specifically 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 100wt%. Ether-based solvents have the characteristics of excellent compatibility with lithium metal, high conductivity, low viscosity and low cost. The first electrolyte is used to form a composite inorganic interface membrane. Using an ether-based solvent as the main solvent is more conducive to improving the stability of the composite inorganic interface membrane, providing a stable chemical environment for the initial operation of the lithium metal battery, and providing a stable foundation for the subsequent formation of a flexible organic membrane.
[0065] Ether-based solvents are divided into two categories: chain ethers and cyclic ethers. Chain ethers include, but are not limited to, dimethyl ether (DME), diethyl ether (DEE), 1,2-methoxypropane (MOP), diethylene glycol dimethyl ether (DEDM), triethylene glycol dimethyl ether (TRIEDM), tetraethylene glycol dimethyl ether (TETREDM), ethyl propyl ether (EPE), and some fluorinated chain ethers; cyclic ethers include, but are not limited to, tetrahydrofuran (THF), 2-methylfuran (2-MF), 1,3-dioxolane (DOL), 4,5-diethyl-1,3-dioxolane, 4,5-dimethyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, 2-methyl-1,3-dioxolane, and 1,4-dioxolane and its fluorinated compounds.
[0066] The non-aqueous organic solvent in the first electrolyte may also include one or more of carbonate organic solvents, phosphate organic solvents, fluorine-containing solvents, sulfone-based solvents, nitrile solvents, dioxolane solvents and ionic liquid organic solvents.
[0067] The carbonate-based organic solvents include, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), trifluoroethyl methyl carbonate (TFMEC), ethyl propyl carbonate (EPC), and methyl propyl carbonate (MPC); the phosphate-based organic solvents include, but are not limited to, trimethyl phosphate (TMP), triethyl phosphate (TEP), and dimethyl ethyl phosphonate; the fluorine-containing solvents include, but are not limited to, fluoroethylene carbonate (FEC), trifluoroethyl methyl carbonate (TFMEC), and other fluorine-modified carbonates, which are concerned for their excellent electrochemical stability and the ability to form high-quality SEI (solid electrolyte interphase) films; the sulfone-based compounds mainly include dimethyl sulfone (DMSO) and diethyl sulfone (DES), which can improve the interface stability and ion transport performance in some high-temperature systems; the nitrile-based compounds include, but are not limited to, acetonitrile (AN), propionitrile (ACN), and adiponitrile (ADN), which are used to improve the ionic conductivity due to their high dielectric constant and low viscosity; the dioxolane-based compounds mainly include γ-butyrolactone (GBL) and δ-valerolactone (NVL), which have good chemical stability and moderate polarity, and can improve the solvent-electrolyte compatibility in some electrolyte systems; the cation of the ionic liquid-based organic solvent can be selected from quaternary ammonium, quaternary phosphonium, imidazole, or pyridine, and the anion can be selected from fluorine-containing inorganic anions (such as BF4 - , PF6 - , FSI - ) or fluorine-containing organic anions (such as TFSI - ). Specific examples include, but are not limited to, 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM PF6), 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM BF4), 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide (BMIM TFSI), 1-butyl-3-methylimidazolium methanesulfonate (BMIM MeSO3), 1-butyl-3-methylimidazolium trifluoroacetate (BMIM TFA), and 1-octyl-3-methylimidazolium hexafluorophosphate (OMIM PF6).
[0068] After step S103, before step S104, a first standing treatment can also be included, in which the battery cell assembly is left to stand at 40-45°C for 36-72h to ensure that the first electrolyte fully wets the positive electrode sheet, the negative current collector, and the separator in the battery cell assembly.
[0069] In step S104, the first formation process includes: charging the battery cell assembly to a state of charge (SOC) greater than or equal to 50% at a first charge rate and a first temperature, for example, 50%, 55%, 60%, 65%, 70%, 75%, or 80%. The first charge rate is 0.01C to 0.2C, for example, 0.01C, 0.05C, 0.08C, 0.1C, 0.13C, 0.16C, 0.18C, or 0.2C. The first temperature is 40°C to 50°C, for example, 40°C, 43°C, 45°C, 46°C, 48°C, or 50°C.
[0070] In step S105, the mass fraction of fluoroethylene carbonate in the second electrolyte can specifically be 5wt%, 8wt%, 10wt%, 13wt%, 18wt%, 20wt%, 24wt%, 26wt%, 28wt%, 30wt%, 33wt% or 35wt%.
[0071] The lithium salt in the second electrolyte can be selected from one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiFSI, LiTFSI, LiTFS, LiDFOB, LiBOB, LiPO2F2, LiDFOP and LiTFOP, preferably one or more of LiPF6, LiBF4, LiBOB, LiDFOB, LiTFSI and LiFSI.
[0072] The mass fraction of the lithium salt in the second electrolyte can be specifically 5wt%, 8wt%, 10wt%, 12wt%, 13wt% or 15wt%.The mass fraction of the lithium salt refers to the ratio of the mass of the lithium salt to the total mass of the second electrolyte.
[0073] The mass fraction of the electrostatic shielding additive in the second electrolyte can specifically be 0.05 wt%, 0.1 wt%, 0.5 wt%, 1 wt%, 3 wt%, 5 wt%, 10 wt%, 13 wt%, 15 wt%, 18 wt% or 20 wt%.
[0074] The electrostatic shielding additive is selected from at least one of an organic quaternary ammonium salt, a metal halide, or an organic ionic liquid. The electrostatic shielding additive balances the local electric field distribution, suppresses the tendency of excessive lithium ion deposition in the protruding area, and blocks the dendrite nucleation path.
[0075] Organic quaternary ammonium salts include tetramethylammonium bromide (TMAB), tetraethylammonium bromide (TEAB), tetrabutylammonium bromide (TBAB), hexadecyltrimethylammonium bromide (CTAB) and benzalkonium bromide; metal halides include aluminum chloride (AlCl3), zinc chloride (ZnCl2), magnesium chloride (MgCl2), calcium chloride (CaCl2) and lithium chloride (LiCl); organic ionic liquids include 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM(PF6)), 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM]BF4), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide (BMIM TFSI), 1-butyl-3-methylimidazolium methanesulfonate (BMIM MeSO3) and 1-butyl-3-methylimidazolium trifluoroacetate (BMIM TFA).
[0076] The mass fraction of the anchoring filler additive in the second electrolyte can specifically be 0.05 wt%, 0.1 wt%, 0.5 wt%, 1 wt%, 3 wt%, 5 wt%, 10 wt%, 13 wt%, 15 wt%, 18 wt% or 20 wt%.
[0077] The anchoring filler additive is selected from at least one of a fullerene derivative, an organosilicon compound, or a carbon-based nanomaterial. This anchoring filler additive can chemically or physically interact with lithium ions on the lithium metal surface, filling interfacial defects and "anchoring" lithium ion deposition, thereby improving the mechanical flexibility and overall stability of the SEI film, thereby further enhancing the cycle life and safety of the anode-free lithium metal battery.
[0078] Fullerene derivatives include hexanitro
[60] -fullerene (C 60 (NO2)6), carboxylated fullerene (C 60 (COOH) x ) and fluorinated fullerenes; organosilicon compounds include γ-aminopropyltriethoxysilane (APTES), N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AEAPTMS) and 3-mercaptopropyltrimethoxysilane (MPTMS); carbon-based nanomaterials include nitrogen-doped graphene, multi-walled carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs) and graphene oxide (GO).
[0079] The non-aqueous organic solvent in the second electrolyte may include an ether-based solvent and a sulfone-based solvent, and the total mass of the ether-based solvent and the sulfone-based solvent accounts for more than 50 wt % of the mass of the non-aqueous organic solvent. 6+), and the S=O bond has an extremely high bond energy, which gives it excellent antioxidant stability and thermal stability. Therefore, it is regarded as a highly promising high-voltage, high-temperature electrolyte solvent. The introduction of sulfone-based solvents into the second electrolyte is beneficial to improving the high-temperature stability of lithium metal batteries.
[0080] In some embodiments, in the second electrolyte, the mass ratio of the ether-based solvent to the sulfone-based solvent is greater than or equal to 1. That is, the ether-based solvent still serves as the main solvent, and the sulfone-based solvent serves as the auxiliary solvent. Due to the poor compatibility of sulfone-based solvents with lithium metal, and the high melting point, high viscosity, and low wettability commonly encountered with sulfone-based solvents, the practical application of sulfone-based solvents has been hindered. Using an ether-based solvent as the main solvent and a sulfone-based solvent as the auxiliary solvent retains the excellent compatibility with lithium metal, high conductivity, low viscosity, and low cost of the ether-based solvent, while also adding the excellent anti-oxidative stability and thermal stability of the sulfone-based solvent. The combination of the two is more conducive to the long-term stable cycling of lithium metal batteries.
[0081] The non-aqueous organic solvent in the second electrolyte may further include one or more of carbonate organic solvents, phosphate organic solvents, fluorine-containing solvents, nitrile solvents, dioxolane solvents and ionic liquid organic solvents.
[0082] After step S105 and before step S106, a second standing treatment may be further included, in which the battery cell assembly is stood at 40° C. to 45° C. for 36 h to 72 h to ensure that the second electrolyte is fully mixed with the first electrolyte and improve the overall uniformity of the electrolyte.
[0083] In step S106, the second formation process includes charging the battery cell assembly to a state of charge greater than 85% at a second charge rate and a second temperature, for example, 85%, 88%, 90%, 93%, 95%, or 100%. The second charge rate is 0.2C to 0.5C, for example, 0.2C, 0.25C, 0.3C, 0.35C, 0.4C, 0.45C, or 0.5C. The second temperature is 40°C to 50°C, for example, 43°C, 46°C, 48°C, or 50°C.
[0084] The first charge rate in the first formation process is lower than the second charge rate in the second formation process, and the first temperature in the first formation process is lower than the second temperature in the second formation process, which is more conducive to the formation of a stable SEI film. The lower charge rate and lower temperature in the first formation process allow lithium ions to migrate slowly and evenly, reduce the risk of dendrites, and are conducive to the formation of a stable composite inorganic interface film. The relatively low temperature can inhibit electrolyte side reactions, promote the formation of a dense and stable solid composite inorganic interface film, and improve the initial coulombic efficiency. The relatively low temperature environment is also conducive to reducing the violent reaction between lithium metal and electrolyte, avoiding excessive growth of the composite inorganic interface film, reducing active lithium loss, and extending cycle life. The higher charge rate and higher temperature in the second formation process can promote electrolyte penetration and ion conduction, repair possible defects in the inorganic interface film in the first formation, and form a more uniform and flexible organic interface layer. The relatively high temperature can accelerate the activation of electrode materials and shorten the aging time. The relatively high charge rate can activate the active substances deep in the electrode and improve capacity utilization.
[0085] In some embodiments, the mass of the first electrolyte accounts for 65wt% to 90wt% of the total mass of the electrolyte, for example, it can be 65wt%, 70wt%, 75wt%, 80wt%, 85wt% or 90wt%. If the injection amount of the first electrolyte is insufficient, the battery cell assembly may not be fully infiltrated, and lithium precipitation problems may occur after formation; if the injection amount of the first electrolyte is too large, it may cause the concentration of additives in the second electrolyte to be too high, thereby causing uneven distribution of additives inside the battery cell assembly. Preferably, the mass of the first electrolyte accounts for 70wt% to 90wt% of the total mass of the electrolyte.
[0086] According to some embodiments of the present application, on the other hand, the embodiments of the present application further provide a lithium metal battery, which is prepared using the manufacturing method of the lithium metal battery in the above embodiment.
[0087] According to some embodiments of the present application, on the other hand, the embodiments of the present application further provide an electrical device, which includes a lithium metal battery and a load as in the above embodiments; or, the electrical device includes an energy storage system and a load, and the energy storage system includes multiple lithium metal batteries as in the above embodiments.
[0088] The lithium metal battery and its manufacturing method and electrical equipment provided in the embodiments of the present application, in the manufacturing method, an inorganic-organic composite interface layer is constructed by injecting electrolyte in stages and the lithium deposition behavior is dynamically regulated. The first injection forms a rigid composite inorganic interface layer, and the second injection superimposes a flexible organic layer and introduces functional additives to systematically solve the problems of interface stability and lithium dendrite growth. Based on the interface dynamic requirements of the negative electrode-free lithium metal battery, the first injection focuses on constructing a high-stability composite inorganic interface layer to reduce the initial side reaction activity; the second injection continuously optimizes the deposition behavior and repairs interface defects through a flexible organic film and dynamic regulation dual path. The collaborative design of the two-step process takes into account both interface rigid support and dynamic adaptability, providing dual guarantees for long-cycle stability and high-rate performance.
[0089] In the first injection process, a first electrolyte consisting of lithium polysulfide (Li2S8), lithium nitrate (LiNO3), lithium salt, and non-aqueous organic solvent is injected into the battery cell assembly, followed by a first formation process. The complementary properties of lithium polysulfide and lithium nitrate are used to form a composite inorganic interface layer. The sulfide layer (Li2S) formed by Li2S8 is mechanically brittle and easily fractured due to stress concentration. The nitride layer (Li3N) formed by LiNO3, while chemically stable, has poor adaptability to volume expansion. Through the synergistic effect of Li2S8 and LiNO3, a sulfur-nitrogen composite mechanism is used to form a Li2S-Li3N cross-linked structure, which combines high ionic conductivity and mechanical toughness. This not only inhibits electrolyte decomposition but also provides a stable foundation for subsequent cycles. In the second injection process, a second electrolyte consisting of fluoroethylene carbonate (FEC), lithium salt, electrostatic shielding additives, anchoring filler additives, and non-aqueous organic solvent is injected into the battery cell assembly, followed by a second formation process. A flexible organic layer is generated through FEC decomposition and coated on the surface of the composite inorganic interface layer to alleviate the stress impact caused by volume changes. Its dynamic repair properties can adapt to the stress changes caused by the volume expansion / contraction of lithium metal, reducing the risk of interfacial film rupture. The second injection process also introduces electrostatic shielding additives and anchoring filler additives. The electrostatic shielding additive releases high-valent cations to neutralize the local electric field distortion in the lithium deposition raised area, balance the local electric field distribution, inhibit the excessive deposition of lithium ions in the raised area, block the dendrite nucleation path and thus block the growth of dendrite tips. The anchoring filler additive guides lithium ions through adsorption and directional deposition at defect sites, preferentially guiding the formation of a dense lithium layer in the depressed area of the interface, promoting a uniform deposition morphology. Electrostatic shielding additives are used to suppress the tip effect, and anchoring filling additives are used to repair interface defects. Electrostatic shielding additives and anchoring filling additives work together to guide the directional deposition of lithium ions through physical confinement and chemical bonding, repairing microscopic defects, not only achieving uniform lithium deposition morphology, but also reducing interface impedance and optimizing ion transfer kinetics. The synergistic effect of electrostatic shielding additives and anchoring filling additives breaks through the limitation of a single type of additive that only regulates local deposition, and reduces interface impedance and optimizes lithium ion transfer kinetics through complementary mechanisms, thereby improving the cycle stability of lithium metal batteries at high rates.
[0090] The following are specific examples of this application.
[0091] Table 1 shows the formulas of the first and second electrolytes for various embodiments provided in the present application. N-1 corresponds to the formula of the first electrolyte, and N corresponds to the number of the embodiment; M-2 corresponds to the formula of the second electrolyte, and M corresponds to the number of the embodiment.
[0092] Table 1
[0093]
[0094] Table 1
[0095]
[0096] DOL is 1,3-dioxolane (non-aqueous organic solvent); DME is ethylene glycol dimethyl ether (non-aqueous organic solvent); EMS is ethyl methanesulfonate (non-aqueous organic solvent); LiPF6 is lithium hexafluorophosphate (lithium salt); LiTFSI is lithium bis(trifluoromethanesulfonyl imide) (lithium salt); Li2S8 is lithium octasulfide (lithium polysulfide); LiNO3 is lithium nitrate; FEC is fluoroethylene carbonate; CsPF6 is cesium hexafluorophosphate (static shielding additive); AlCl3 is aluminum chloride (static shielding additive); C 60 (NO2)6 is hexanitro
[60] -fullerene (anchoring filler additive).
[0097] In Table 1, the solvent is shown as the percentage of the total mass of the solvent, and the remaining lithium salts and additives are the mass percentages of the overall formula. For example, in Example 17, taking the mass of the first electrolyte as 100g, the mass calculation method of each component in the first electrolyte is: the mass of LiPF6 is 8%×100g=8g, the mass of LiTFSI is 5%×100g=5g, the mass of Li2S8 is 2%×100g=2g, the mass of LiNO3 is 2%×100g=2g, and the total mass of the solvent is (100g-mass of additives-mass of lithium salts)=(100g-8g-5g-2g-2g)=83g, then DO The mass of L in the first electrolyte is 83g×50%=41.5g, and the mass of DME in the first electrolyte is 83g×50%=41.5g. Taking the mass of the second electrolyte as 100g as an example, the calculation method of each component in the second electrolyte is: the mass of LiPF6 is 8%×100g=8g, the mass of LiTFSI is 5%×100g=5g, the mass of FEC is 33.3%×100g=33.3g, the mass of AlCl3 is 33.3%×100g=33.3g, and the mass of C is 100g. 60 The mass of (NO2)6 is 0.3%×100g=0.3g, and the total mass of the solvent is (100g-mass of additive-mass of lithium salt)=(100g-8g-5g-33.3g-33.3g-0.3g)=20.1g. Then, the mass of DOL in the second electrolyte is 20.1g×50%=10.05g, and the mass of DME in the second electrolyte is 20.1g×50%=10.05g. The calculation method of the first electrolyte or the second electrolyte in other embodiments is similar and will not be repeated here.
[0098] The injection ratio of the first electrolyte and the second electrolyte used in Examples 1 to 18 is 85:15.
[0099] The lithium metal batteries corresponding to Examples 1 to 18 were prepared using the following method.
[0100] S201. Provide a positive electrode sheet, a negative electrode current collector and a separator. The positive electrode sheet includes an aluminum foil and a positive electrode material layer covering the aluminum foil. The positive electrode material layer is composed of lithium iron phosphate, a conductive agent SuperP, carbon nanotubes (CNT) and polyvinylidene fluoride (PVDF) in a mass ratio of 95.8:1:0.7:2.5; the negative electrode current collector is copper foil; and the separator is a PP separator.
[0101] S202, winding the positive electrode sheet, the negative electrode current collector and the separator, and placing them into the aluminum-plastic film shell, baking to remove moisture to form a battery cell assembly.
[0102] S203 , performing a first liquid injection process on the battery cell assembly, injecting a first electrolyte into the battery cell assembly. The composition of the first electrolyte is shown in Table 1.
[0103] S204. After the battery cell assembly is left to stand at 45°C for 36 hours, the battery cell assembly is subjected to the first formation process. The battery cell assembly is charged with a rate current of 0.05C to a SOC of 50% and then discharged. The upper limit voltage is 3.65V and the temperature is 40°C.
[0104] S205 , performing a second liquid injection process on the battery cell assembly, injecting a second electrolyte into the battery cell assembly. The composition of the second electrolyte is shown in Table 1.
[0105] S206. After the battery cell assembly is left standing at 45°C for 36 hours, the battery cell assembly is subjected to a second formation process. The battery cell assembly is charged with a rate current of 0.3C to a SOC of 85% and then discharged. The upper limit voltage is 3.65V and the temperature is 45°C.
[0106] The lithium metal batteries of each embodiment were subjected to a 25° C. cycle capacity retention test and a 45° C. cycle capacity retention test. The test results are shown in Table 2.
[0107] Table 2
[0108]
[0109] (1) 25℃ cycle capacity retention test: At 25℃, charge the lithium metal battery to the upper limit voltage at a constant current of 0.5C / 1.5C, then charge it to a current of 0.05C at a constant voltage, and then discharge it to the lower limit voltage at a constant current of 0.5C / 1.5C. Perform 200 cycles of charge and discharge tests. Record the first-week efficiency, the 100th cycle capacity retention rate, and the 200th cycle capacity retention rate. The nth cycle capacity retention rate = (nth discharge capacity / first discharge capacity) × 100%, the first-week efficiency (%) = (first cycle discharge capacity / first cycle charge capacity) × 100%.
[0110] (2) 45°C cycle capacity retention test: At 45°C, charge the lithium metal battery to the upper limit voltage at a constant current of 0.5C / 1.5C, then charge it at a constant voltage to a current of 0.05C, and then discharge it to the lower limit voltage at a constant current of 0.5C / 1.5C. Perform 200 cycles of charge and discharge tests. Record the first-week efficiency, the 100th cycle capacity retention rate, and the 200th cycle capacity retention rate. The nth-cycle capacity retention rate = (nth-cycle discharge capacity / first-cycle discharge capacity) × 100%, the first-cycle efficiency (%) = (first-cycle discharge capacity / first-cycle charge capacity) × 100%.
[0111] Through key indicators such as room temperature cycle capacity retention rate, high temperature cycle capacity retention rate and first-week efficiency at different rates of 0.5C and 1.5C, we can deeply explore the impact of electrolyte formulation and injection method on battery performance.
[0112] In the room temperature cycle and high temperature cycle tests at 0.5C and 1.5C, the comparison results of Example 1 and Example 2 show that the addition of the additive significantly improves the capacity retention rate and first cycle efficiency under room temperature and high temperature conditions. LiNO3 generates a nitrogen-containing inorganic passivation layer (such as Li3N and LiN) after reduction on the lithium metal surface. x O y ), enhance the mechanical strength and chemical stability of the interface, and reduce the side reaction rate between the electrolyte and metallic lithium. Li2S8 decomposes at the interface to form sulfides (such as Li2S), constructing an inorganic protective layer with low solubility and high lithium conductivity, improving the interface ion transport performance and inhibiting side reactions. At the same time, FEC decomposes on the lithium surface to form fluorine-rich compounds (such as LiF), whose high mechanical toughness and chemical stability can effectively block electron transmission and prevent the continuous decomposition of the electrolyte. The three work synergistically to form Li3N / LiN x O y , Li2S and LiF composite SEI film, guides the uniform deposition of lithium, inhibits dendrite growth, reduces interface impedance, and significantly improves Coulombic efficiency and cycle life.
[0113] Overall data shows that the capacity retention of anode-free lithium metal batteries under high-temperature cycling is better than that under normal temperature conditions, while an increase in the rate leads to a decrease in the capacity retention rate. This is because high temperature reduces the viscosity of the electrolyte, increases the ion diffusion rate, and promotes the formation of a more uniform and stable SEI film, thereby improving the cycling performance. At high rates, however, due to insufficient local lithium ion supply and excessively fast deposition rate, uneven lithium deposition and dendrite growth are easily caused, thereby reducing the cycling stability.
[0114] Comparative Example 2 to Example 8, the secondary injection method is better than the primary injection method in various performance indicators, but the order and collocation of different additives affect the final performance. The formulation of Example 6 (containing Li2S8 and LiNO3 in the first electrolyte and FEC in the second electrolyte) exhibits the best cycle capacity retention rate and first week efficiency at different temperatures and rates.
[0115] Inorganic film-forming additive Li2S8 and LiNO3 build an initial stable inorganic SEI layer through a sulfur-nitrogen composite passivation mechanism in the first charge-discharge stage. Li2S8 reacts with lithium metal in the electrolyte to form sulfides such as Li2S and Li2S2, which are embedded in the SEI film, enhancing its mechanical toughness and chemical stability. LiNO3 is preferentially reduced on the lithium surface to form an inorganic passivation layer mainly composed of Li3N and LiN x O y The inorganic passivation layer mainly composed of Li3N and LiN
[0116] In the long cycle process, the organic film-forming additive FEC is introduced, and the flexible polymer layer generated by its decomposition enhances the anti-expansion ability of the SEI, prevents the interface film from breaking, and reduces side reactions. In addition, FEC regulates the solvation sheath structure, increases the coordination number of anions, reduces the desolvation energy barrier of lithium ions, and improves the uniformity and reversibility of lithium deposition. Through the inorganic-organic staged film-forming strategy, the SEI structure is stably constructed in the early stage and dynamically repaired in the long cycle process, so that the interface stability, coulombic efficiency and cycle life of the battery are significantly improved.
[0117] The comparative data of Example 6, Example 9, Example 10, Example 11, and Example 12 show that the electrostatic shielding additives CsPF6 and AlCl3 significantly improve the battery performance, and the addition effect in the second electrolyte is better than that in the first electrolyte. This may be because the secondary injected electrolyte mainly exists in the free state, at which time the introduction of electrostatic shielding additives can more effectively regulate the local electric field distribution and ion transport environment. These additives form a positive charge shielding layer in the lithium deposition protrusion area, inhibiting the excessive deposition of local lithium ions and subsequent dendrite growth.
[0118] A comparison of Example 12 and Example 13 shows that the final effect of using two electrostatic shielding additives with similar mechanisms (such as CsPF6 and AlCl3) is not much different from that of using one of them alone. When one additive has reached the saturation state of regulation, further adding another additive with a similar mechanism of action will not significantly enhance the overall effect. This shows that there is a "saturation point" for the electrostatic shielding effect, and additional additions beyond this concentration do not bring additional performance improvements. Therefore, in battery design, the type and amount of electrostatic shielding additives can be appropriately selected according to specific performance requirements and system characteristics, without the need to pursue diversification of additive types or excessive addition.
[0119] The comparative data of Example 6, Example 14 and Example 15 show that the anchoring filler additive C 60 The addition of (NO2)6 also significantly improves battery performance, and its effect in the second electrolyte is better than that in the first electrolyte.
[0120] C 60 The mechanism of action of (NO2)6 stems from the spatial confinement effect of its rigid fullerene skeleton and the dynamic chemical adaptation characteristics of the surface nitro group. Its spherical skeleton is preferentially adsorbed on the microscopic depressions on the electrode surface through van der Waals forces, forming a nanoscale physical barrier, which promotes the deposition of lithium ions in low curvature areas, thereby inhibiting dendrite growth. At the same time, its nitro group (-NO2) undergoes a directionally chemical bond with the unpaired electrons on the surface of lithium metal, anchoring them in active sites such as grain boundary defects or dislocations, inhibiting local lithium ion aggregation. During the cycle, the nitro group undergoes a reduction reaction (-NO2→-NHO→-NH2), accompanied by electron release, to repair the SEI film in situ. At the same time, the generated amino group (-NH2) enhances the lithium ion affinity of the interface layer and promotes uniform lithium deposition.
[0121] Under the secondary injection strategy, the inorganic SEI skeleton (Li2S8 / LiNO3 synergistic effect) in the first film formation stage has formed a high modulus substrate. 60 (NO2)6 can migrate to dynamic defects on the interface (such as deposition front or stress cracks) through concentration gradient, and through the synergistic effect of physical filling and chemical bonding, it can achieve "defect identification-in situ repair-structural strengthening" in the mature stage of SEI, thereby optimizing interface stability.
[0122] The data of Example 16 and Example 17 show that the electrostatic shielding additive and the anchoring filler additive used in combination in the second electrolyte can achieve the best performance, especially under high rate conditions, the cycle attenuation is significantly slowed down.
[0123] The synergistic optimization of the two types of additives is based on cross-scale dynamic interface regulation. Electrostatic shielding additives form a dynamic potential buffering effect through high-valent cations, weakening the local electric field distortion at the electrode / electrolyte interface at the mesoscopic scale, suppressing the uneven distribution of lithium ion flux at high rates, and reducing the kinetic driving force of dendrite nucleation. Anchoring filler additives, on the other hand, optimize the lithium deposition path and repair SEI film damage at the microscale by leveraging the rigid confinement effect of fullerene derivatives and the dynamic response characteristics of functional groups. The synergy between the two is reflected in "time-space dual-dimensional regulation": during instantaneous current shock, electrostatic shielding additives guide lithium ions to diffuse to low-energy sites; during continuous deposition, anchoring filler additives dynamically repair interface cracks and promote uniform deposition. This synergistic mechanism optimizes the uniformity of lithium deposition morphology and the stability of interface structure, significantly reducing the capacity decay rate caused by local lithium depletion under high-rate conditions.
[0124] The data of Example 18 show that the high-temperature cycle performance of the lithium metal battery is improved after introducing an appropriate amount of sulfone-based solvent into the second electrolyte.
[0125] Those skilled in the art will appreciate that the above-described embodiments are specific examples for implementing the present application, and that in actual applications, various changes in form and detail may be made thereto without departing from the spirit and scope of the present application. Any person skilled in the art may make various changes and modifications without departing from the spirit and scope of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined in the claims.
Claims
1. A method for manufacturing a lithium metal battery, characterized in that: include: Providing a positive electrode sheet, a negative electrode current collector and a separator, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer; The positive electrode sheet, the negative electrode current collector and the separator are wound or stacked and then placed in a housing to form a battery cell assembly, with the separator being located between the positive electrode sheet and the negative electrode current collector; Performing a first liquid injection process on the battery cell assembly to inject a first electrolyte into the battery cell assembly, wherein the first electrolyte comprises components of lithium polysulfide, lithium nitrate, lithium salt, and a balance of a non-aqueous organic solvent; performing a first formation process on the battery cell assembly; Performing a second liquid injection process on the battery cell assembly to inject a second electrolyte into the battery cell assembly, wherein the components of the second electrolyte include: fluoroethylene carbonate, lithium salt, electrostatic shielding additive, anchoring filling additive and balance non-aqueous organic solvent; The battery cell assembly is subjected to a second formation process.
2. The method for manufacturing a lithium metal battery according to claim 1, wherein: The non-aqueous organic solvent in the first electrolyte includes an ether-based solvent, and the mass ratio of the ether-based solvent to the mass ratio of the non-aqueous organic solvent is greater than 50 wt %.
3. The method for manufacturing a lithium metal battery according to claim 1 or 2, wherein: The non-aqueous organic solvent in the second electrolyte includes an ether-based solvent and a sulfone-based solvent, and the total mass of the ether-based solvent and the sulfone-based solvent accounts for more than 50 wt % of the mass of the non-aqueous organic solvent.
4. The method for manufacturing a lithium metal battery according to claim 3, wherein: In the second electrolyte, the mass ratio of the ether-based solvent to the sulfone-based solvent is greater than or equal to 1.
5. The method for manufacturing a lithium metal battery according to claim 1, wherein: The first formation process comprises: charging the battery cell assembly at a first charge rate and a first temperature to a state of charge greater than or equal to 50%; The second formation process includes: charging the battery cell assembly at a second charge rate and a second temperature to a state of charge greater than 85%; The first charging rate is lower than the second charging rate, and the first temperature is lower than the second temperature.
6. The method for manufacturing a lithium metal battery according to claim 5, wherein: The first charging rate is 0.01C to 0.2C; the second charging rate is 0.2C to 0.5C; the first temperature is 40°C to 50°C; and the second temperature is 40°C to 50°C.
7. The method for manufacturing a lithium metal battery according to claim 1, wherein: The anchoring filling additive is selected from at least one of fullerene derivatives, organosilicon compounds or carbon-based nanomaterials.
8. The method for manufacturing a lithium metal battery according to claim 1, wherein: The electrostatic shielding additive is selected from at least one of an organic quaternary ammonium salt, a metal halide or an organic ionic liquid.
9. The method for manufacturing a lithium metal battery according to claim 1, wherein: In the first electrolyte, the mass ratio of the lithium polysulfide is 0.1 wt% to 5 wt%, the mass ratio of the lithium nitrate is 0.1 wt% to 5 wt%, and the mass ratio of the lithium salt is 5 wt% to 15 wt%.
10. The method for manufacturing a lithium metal battery according to claim 1, wherein: In the second electrolyte, the mass ratio of the fluoroethylene carbonate is 5wt% to 35wt%, the mass ratio of the lithium salt is 5wt% to 15wt%, the mass ratio of the electrostatic shielding additive is 0.05wt% to 20wt%, and the mass ratio of the anchor filling additive is 0.05wt% to 20wt%.
11. A lithium metal battery, characterized in that: The lithium metal battery is prepared by the method for manufacturing a lithium metal battery according to any one of claims 1 to 10.
12. An electrical device, characterized in that: The electrical equipment includes the lithium metal battery as claimed in claim 11 and a load; or, the electrical equipment includes an energy storage system and a load, and the energy storage system includes multiple lithium metal batteries as claimed in claim 11.